Perception, motivation and performance of students in food preservation technology course through game-based and gamification approach / Nurul Asyikin Md Zaki and Atikah Kadri - Md Zaki, Nurul Asyikin; Kadri, Atikah (UiTM Press, 2020)
Interactive learning that involves students participation and cooperation has been reported to help develop creativity, problem-solving and critical thinking skills, which are among top ten skills needed in 2020. The incorporation of game-based and gamification in teaching and learning is an interesting approach to enhance students learning abilities and skills acquisition through fun and immersive learning experience. This study aims to examine the implications of game-based and gamification of learning towards students perception, motivation and performance in engineering students particularly for those who attended the Food Preservation Technology course. Positive improvements were seen through the implementation of the game-based and gamification of learning. Findings show that game-based and gamification prepared students with better grasp and retention of knowledge, hence they achieved better grades at the end of the semester compared to students that involved in traditional classroom teaching method.